Perbandingan Analisis Two Way Slab With Beam dengan Flat Slab (Studi Kasus: Coal Yard PLTU Kalimantan Barat) - Syamsi, Muhammad Ibnu (Semesta Teknika, 2015)
Floor slab of coal yard as a storehouse was designed as two way slab with beam and flat slab in order to compare those two systems based on needs of materials and ease of implementation. The design process is based on the provision of SNI 03-2847-2002. Through the design results and analysis of material requirements can be concluded that the need for concrete material on a flat slab system is 2.1% greater than on the two way slab with beam. Meanwhile the steel material requirements for flat slab system is 9.7% greater than two way slab with beam. However, in term of ease of implementation, relatively flat plate systems are superior to the briquette plate system because the number of items of work a little more